2002
DOI: 10.3133/ofr02268
|View full text |Cite
|
Sign up to set email alerts
|

Porphyry copper deposits of the world: Database, maps, and preliminary analysis

Abstract: mineralization or alteration within two (2) kilometers was combined into one deposit. Some examples illustrate the effects of the application of this rule. In many other lists of mineral deposits, Chuqui Norte, Exotica, Radomiro Tomic (Pampa Norte), and Chuquicamata in Chile are reported as separate deposits, whereas, here they are reported as one because of the two kilometer rule. El Pachon in Argentina and Los Pelambres in Chile are two parts of the same deposit, frequently reported as separate deposits. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 2 publications
0
24
1
1
Order By: Relevance
“…5c), although the quality and accuracy of Au data must be treated with caution. For instance at Kadjaran, depending on the source of data (Table 1), the reported Au contents vary from 0.65 g/t (Singer et al, 2002) to 0.02 g/t (data communicated by the mine staff). In addition, further studies are required to understand if the reported Au grades are intimately associated with the porphyry event or…”
Section: Relationships Between the Magmatic-geodynamic Evolution And mentioning
confidence: 99%
“…5c), although the quality and accuracy of Au data must be treated with caution. For instance at Kadjaran, depending on the source of data (Table 1), the reported Au contents vary from 0.65 g/t (Singer et al, 2002) to 0.02 g/t (data communicated by the mine staff). In addition, further studies are required to understand if the reported Au grades are intimately associated with the porphyry event or…”
Section: Relationships Between the Magmatic-geodynamic Evolution And mentioning
confidence: 99%
“…The following subtypes of porphyry deposits are defined according to the metal abundance (Sinclair, 2008 From a geological perspective, porphyry copper deposits are considered to be one of the best-understood classes of hydrothermal systems operating above a crystallizing magma chamber which may have intruded its coeval stratovolcano (Hedenquist and Richards, 1998). , defines porphyry copper systems as large volumes (10 to >100 km 3 ) of hydrothermally altered rock centered on porphyry copper stocks that may also contain skarn, carbonate-replacement, sediment-hosted, and intermediate to the high sulfidation epithermal base and precious metal mineralization.…”
Section: Porphyry Depositsmentioning
confidence: 99%
“…"In many porphyry deposits, alteration zones on a deposit scale consist of an inner potassic zone characterised by biotite and/or potassium-feldspar (± amphibole ± magnetite ± anhydrite) and an outer zone of propylitic alteration that consists of quartz, chlorite, epidote, calcite and, locally, albite associated with pyrite. Zones of phyllic alteration (quartz + sericite + pyrite) and argillic alteration (quartz + illite + pyrite ± kaolinite ± smectite ± montmorillonite ± calcite) may be part of the zonal pattern between the potassic and propylitic zones, or can be irregular or tabular, and younger zones could be superimposed on older alteration and sulphide assemblages (e.g., Ladolam; )" (Sinclair, 2008;p8). deposits.…”
Section: Porphyry Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…10.7 Mt, including 5.4 Mt in the USA, 2.5 Mt in Chile, 0.91 Mt in Canada, 0.36 Mt in Russia, and 1.67 Mt in other regions of the world (Ray 1995;Singer 1995;Kirkham and Sinclair 1996;Laznicka 1999;Mutschler et al 2000;Singer et al 2002). Based on the reserve data provided by the China National Mineral Resources Committee, Mo deposits in China can be classified into giant (.0.5 Mt), large (0.1-0.5 Mt), medium (0.01-0.1 Mt), or small (,0.01 Mt;Zhu 1999).…”
Section: Introductionmentioning
confidence: 98%